WKB SOLUTIONS FOR QUANTUM MECHANICAL GRAVITATIONAL POTENTIAL PLUS HARMONIC OSCILLATOR POTENTIAL. Issue 3 (2017) - Louis, H.; Ita, B. I.; Nzeata-Ibe, N. A.; Amos, P. I.; Joseph, I.; Ikot, A. N; Magu, T. O.
No abstract available